Improved Management of the Advanced Nonseminomatous Testis Cancer - Vugrin, Davor (Revista Brasileira de Cancerologia, 2023)
With the VAB-6 program about 90% (54/59) of patients with stage III and bulky stage II disease achieved complete remission and eighty percent remain free of disease. Patients with minimal metastatic disease can usually be treated successfully with chemotherapy alone, while patients with advanced disease frequently required combined treatment with chemotherapy and surgery in order to achieve complete remission. Most patients without a teratomatous component in the testis tumor will achieve complete remission with chemotherapy alone, whereas patients with a teratomatous componente are more likely to require the combined approach of chemotherapy and surgery to achieve disease free status. Pure seminoma was apparently the most responsive and pure choriocarcinoma the least responsive histologic type of testis tumor to the combination chemotherapy. The incidence of a residual mature teratoma in the resected specimem has increased with the improved efficacy of chemotherapy. High complete remission rates and a short duration of treatment ensure rapid return of afflicted individuals to productive life, thus, fulfilling a most importante goal of treatment.